2013
DOI: 10.1128/iai.01234-12
|View full text |Cite
|
Sign up to set email alerts
|

Estrogenic Modulation of Uropathogenic Escherichia coli Infection Pathogenesis in a Murine Menopause Model

Abstract: Recurrent urinary tract infections (UTIs), primarily caused by uropathogenic Escherichia coli (UPEC), annually affect over 13 million patients in the United States. Menopausal women are disproportionally susceptible, suggesting estrogen deficiency is a significant risk factor for chronic and recurrent UTI. How estrogen status governs susceptibility to UTIs remains unknown, and whether hormone therapy protects against UTIs remains controversial. Here, we used a mouse model of surgical menopause by ovariectomy a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
53
2
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 53 publications
(63 citation statements)
references
References 54 publications
4
53
2
2
Order By: Relevance
“…Thus, excessive exfoliation might eventually turn into an infection-promoting effect. In addition, delayed and incomplete differentiation of the basal cell layers in the absence of estrogen was recently demonstrated in the mouse urinary tract during E. coli infection (41). We furthermore speculated that the strength of cell-cell contacts influences the disposition of urothelial cells to exfoliation after pathogen-induced apoptosis in single umbrella cells.…”
Section: Discussionmentioning
confidence: 94%
“…Thus, excessive exfoliation might eventually turn into an infection-promoting effect. In addition, delayed and incomplete differentiation of the basal cell layers in the absence of estrogen was recently demonstrated in the mouse urinary tract during E. coli infection (41). We furthermore speculated that the strength of cell-cell contacts influences the disposition of urothelial cells to exfoliation after pathogen-induced apoptosis in single umbrella cells.…”
Section: Discussionmentioning
confidence: 94%
“…Other microbial niches, such as the vaginal tract, are greatly altered in the absence of estrogen. Given that estrogen alters the bladder epithelium [33, 34], and that estrogen improves the incidence of UTIs [3537] and urgency urinary incontinence (UUI) [3840], it is very likely that the microbiome will be altered following menopause which could be a contributing factor to many lower urinary tract symptoms associated with age.…”
Section: Future Directionsmentioning
confidence: 99%
“…A recent study found that vaginal estradiol therapy in post-menopausal women altered the expression of antimicrobial peptides and cell junction proteins in epithelial cells isolated from voided urine, suggesting that estrogen therapy modulates the mucosal barrier of the lower urinary tract (240). In support of these translational findings, several studies of experimental UTI in ovariectomized mice have demonstrated that altering estrogen levels has profound effects on UTI pathogenesis (240242). Thus, vaginal estrogen therapy remains a safe and viable therapeutic option for post-menopausal women suffering from rUTI.…”
Section: Translating Discoveries In Pathogenesis: the Development Of mentioning
confidence: 78%